Monetary policy and the resilience of the German banking system: From Deutsche Bundesbank to ECB - Tim Florian Sepp; Karl-Friedrich Israel; Benjamin Treitz; Tom Hartl (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2024)
The resilience of the German banking system is studied on the semiaggregated level from 1968 to 2022. We distinguish between Large Banks, Regional Banks, Landesbanken, Sparkassen and Credit Unions and study their z-scores as a measure of resilience in response to the monetary policy stances of the Bundesbank and the ECB, respectively. We estimate two-way fixed effects panel regression models for both periods separately. The results suggest that monetary policy was more effective in enhancing resilience during the period of a national currency controlled by the Deutsche Bundesbank. The effect across bank types is much more heterogeneous after the inception of the ECB. In particular, decreasing resilience of Large Banks is associated with expansionary (un)conventional monetary policy in recent years.
Keywords: E42; E52; G21; 330; Resilience; Monetary Policy; Banking; Financial Stability; Germany; Deutsche Bundesbank; ECB; Credit Union; Sparkasse